A maize LIPID TRANSFER PROTEIN may bridge the gap between PHYTOCHROME-mediated light signaling and cuticle biosynthesis. (1st September 2020) - Qiao, Pengfei; Bourgault, Richard; Mohammadi, Marc; Gore, Michael A.; Molina, Isabel; Scanlon, Michael J.
ABSTRACT: Plant epidermal cuticles are composed of hydrophobic lipids that provide a barrier to non-stomatal water loss, and arose in land plants as an adaptation to the dry terrestrial environment. The expanding maize adult leaf displays a dynamic, proximodistal gradient of cuticle development, from the leaf base to the tip. Recently, our gene co-expression network analyses together with reverse genetic analyses suggested a previously undescribed function for PHYTOCHROME-mediated light signaling during cuticular wax deposition. The present work extends these findings by identifying a role for a specific LIPID TRANSFER PROTEIN (LTP) in cuticle development, and validating it via transgenic experiments in Arabidopsis. Given that LTPs and cuticles both evolved in land plants and are absent from aquatic green algae, we propose that during plant evolution, LTPs arose as one of the innovations of land plants that enabled development of the cuticle.